200 kV pulse generator for a power supply of the electron gun for the complex VEPP-5 preinjector - Akimov, V.E.; Kazarezov, I.V.; Korepanov, A.A. (Вопросы атомной науки и техники, 1999)
A 200 kV DC power source on the base of a high-voltage cascade generator [1] is used for a power supply of the electron gun for the VEPP-5 complex preinjector. Advantages of the circuit with DC power supply are its relative simplicity and small power consuming from an AC line. However, a fixed voltage applied to the gun at a beam current of 10 А causes frequent vacuum insulation breakdowns, which decrease its electrical strength. Therefore a problem was stated to develop a high-voltage pulse generator, which will allow us to increase an electrical strength. Furthermore, a small capacitance of the pulse transformer and so less stored energy reduce probability of failure of the gun’s electrodes during its breakdown.